Multiorgan crosstalk in MASLD/MASH: from hepatic pathogenesis to systemic complications - Bai, Wenhua; Zhu, Zheng (Frontiers in Endocrinology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) has evolved from a hepatic-centric condition to a systemic metabolic disorder, with multisystem complications driving clinical outcomes. This review comprehensively examines the pathogenesis and extrahepatic manifestations of MASLD, focusing on interorgan crosstalk. We first delineate the hepatic progression from steatosis to fibrotic metabolic dysfunction-associated steatohepatitis (MASH), emphasizing lipotoxicity, mitochondrial dysfunction, and inflammatory cascades. Subsequently, we analyze key extrahepatic axes (1): the liver-brain axis, where neuroinflammation and cognitive impairment are linked to hepatic metabolic disturbances (2); the gut-liver axis, highlighting roles of gut microbiota dysbiosis and intestinal permeability in disease progression; and (3) the liver-kidney axis, exploring shared fibrotic mechanisms and functional decline. Common pathways-including chronic inflammation, oxidative stress, and immune-metabolic dysregulation-underpin these systemic complications. Therapeutically, we advocate a shift from isolated liver-targeted approaches to integrated multisystem strategies. This review underscores the imperative to reconceptualize MASLD as a systemic disease, necessitating collaborative efforts to refine diagnostic frameworks and therapeutic paradigms for improving patient outcomes.